(untitled) (Research, Society and Development, 2022)
This article aims to analyze the bioethical issues in the health area facing Covid-19. It is a proposal for reflection, with a qualitative descriptive approach, on bioethical analysis against Covid-19 in a dialogue based on the principles that contextualize it, which are: beneficence, autonomy and justice. This article is based on the following discussions: bioethical issues about violence against the elderly in the Covid-19 Pandemic; the autonomy of the cancer client from the perspective of bioethics during the Covid-19 Pandemic and the bioethical analysis in the Covid-19 Pandemic. The challenges of bioethics in relation to issues related to the right to autonomy and access to health services enunciate public health problems in the Brazilian panorama, but highlight a necessary warning to rethink the population’s care practices through public policies. To broaden the discussions, research on Covid-19 with a bioethical approach is recommended without intending to exhaust but broaden the discussions, highlighting other relevant themes about Covid-19 with regard to human dignity.